Knowledge about sexually transmitted infections among users of a testing and counseling center - Aguiar, Cláudia de Azevedo; Bernardes, Alexia Borges; Souto, Isabela Alves Ferreira; Silva-Costa, Aline (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: Sexually Transmitted Infections (STI) are configured as a public health problem, carrying a stigma, and often making the individual more vulnerable to other diseases. The perception of vulnerability does not motivate a preventive behavior towards STIs. Objective: To evaluate knowledge about STIs in relation to sociodemographic aspects and sexual and reproductive behaviors. Methods: This descriptive study was conducted in 2018 with 772 users of the voluntary Testing and Counseling Center (TCC) of Uberaba/MG, and included a questionnaire on their knowledge regarding STIs, addressing specific aspects of HIV, HPV, herpes, gonorrhea, chlamydia, hepatitis B and syphilis. Furthermore, data on the sexual and reproductive behavior of users was collected. Results: The study included 201 men and 571 women, of which 334 were pregnant. Less knowledge about STIs was observed among pregnant women, adolescents and the elderly people. Questions about chlamydia represented the highest rate of errors (75.9%) among respondents, while syphilis was the STI with greater knowledge (79.5% of the correct answers). Most participants reported they had never used condoms (60.5%) and identified “will not get any STI” as the main reason for not using them (52.7%). There were no significant associations between the degree of knowledge of STIs and sexual behavior. Conclusion: Among the population, especially teenagers and elderly people, there is a relevant lack of knowledge when it comes to STIs. Promoting universal access to diagnosis and prevention of STIs, as well as holistic care for vulnerable and at-risk populations, remain as challenges to be overcome.